2008
DOI: 10.1159/000172969
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Decompression of Supratentorial Arachnoid Cysts in Pediatric Patients Younger than One Year

Abstract: Background: There has been much debate about the optimal surgical management of arachnoid cysts in infants younger than 1 year of age. The authors present the clinical and neuroimaging findings in pediatric patients with supratentorial arachnoid cysts treated by surgical decompression. Methods: A retrospective chart review was conducted to identify all pediatric patients who had been diagnosed with arachnoid cysts since 2003. Five infants with symptomatic supratentorial arachnoid cysts underwent surgery at Kan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…28,29,31,37,45,48,55,58,68,69,72,79,80,84,105 Shunt placement carries the additional risk of shunt dependency and overdrainage. 51,62,79 In a recent review of published cases of endoscopic treatment of middle cranial fossa arachnoid cysts, Johnson et al 43 found that this treatment resulted in subdural hygromas and subdural hematomas in 9% and 5% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28,29,31,37,45,48,55,58,68,69,72,79,80,84,105 Shunt placement carries the additional risk of shunt dependency and overdrainage. 51,62,79 In a recent review of published cases of endoscopic treatment of middle cranial fossa arachnoid cysts, Johnson et al 43 found that this treatment resulted in subdural hygromas and subdural hematomas in 9% and 5% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment of posterior fossa cysts may occasionally result in iatrogenic hindbrain herniation. 22,51,62 Although any surgical technique to address an arachnoid cyst may result in complication, the preference for any given surgical technique over another has been debated 15,31,45,55,73,79,105 and is beyond the scope of this article.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent reports have questioned the benefits of surgical interventions for asymptomatically enlarged arachnoid cysts and stated that such enlargements almost always stop spontaneously, and the children are neurologically normal. 4,12,20 It is our cur- rent policy not to operate on patients with asymptomatic enlargement of a suprasellar arachnoid cyst. Suprasellar arachnoid cysts are a well-known cause of hypothalamic-pituitary dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…4,[11][12][13][14][15] In patients with asymptomatic ACs, conservative management with or without serial neuroimaging and neuropsychological follow-up has been advocated, even for those in whom neuroimaging suggests raised intracranial pressure (ICP) 1,2,7,8,10,12,[16][17][18][19][20] from mass effect with compression, shifting, or effacement of cerebral structures. For those with moderate and unspecific symptoms, surgical treatment for ACs is a controversial issue, with many authors expressing reluctance to operate on patients unless the symptoms were dramatic [21][22][23][24][25][26][27][28][29][30][31] while others have been more liberal and suggested that surgical cyst decompression improved 86% of patients with complication rates of 17%. 23 Criteria referring to indications for surgery were individualized per surgeon's judgment, which was very heterogeneous.…”
Section: Introductionmentioning
confidence: 99%